(untitled) - Michael Gudger (Rome, 1999)
This book, the production of which was initiated in this Division, attempts to address the main issues with guarantee funds, and the advantages and disadvantages of traditional guarantee systems. It comes to the broad conclusion that there are few instances in which a traditional loan guarantee service adds value in a sustainable way. The book then considers some examples from a highly developed economy, where guarantees are structured in such a way as to make them economically attractive to all concerned, and draws more general lessons from these examples.
Keywords: agricultural credit